2014
DOI: 10.1016/j.foodchem.2014.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, organic acids and antioxidant activity of grape juices produced from new Brazilian varieties planted in the Northeast Region of Brazil

Abstract: The phenolic compounds, organic acids and the antioxidant activity were determined for grape juice samples from new Brazilian varieties grown in the Sub-middle São Francisco Valley in the Northeast Region of Brazil. The results showed that the Brazilian grape juices have high antioxidant activity, which was significantly correlated with the phenolic compounds catechin, epicatechin gallate, procyanidin B1, rutin, gallic acid, caffeic acid, p-coumaric acid, pelargonidin-3-glucoside, cyanidin-3-glucoside, cyanidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
146
3
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(188 citation statements)
references
References 34 publications
28
146
3
11
Order By: Relevance
“…It was found that the major organic acid was malic acid in studied soft drinks and it represented more than 90% of total acidity in carbonated drinks and ice tea and 85% of that of sherbet. It was reported that the organic acid distribution related to concentrate additive was affected by various factors including koruk maturity, variety, climate, location and processing technology (12,17,21,32). In current study, the usability of koruk juice in the production of ice tea, carbonated drink and sherbet was evaluated.…”
Section: Organic Acid Profile Of Soft Drinksmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that the major organic acid was malic acid in studied soft drinks and it represented more than 90% of total acidity in carbonated drinks and ice tea and 85% of that of sherbet. It was reported that the organic acid distribution related to concentrate additive was affected by various factors including koruk maturity, variety, climate, location and processing technology (12,17,21,32). In current study, the usability of koruk juice in the production of ice tea, carbonated drink and sherbet was evaluated.…”
Section: Organic Acid Profile Of Soft Drinksmentioning
confidence: 97%
“…Moreover, these are sources of organic acid and have antimicrobial effects. For this reasons, different researchers carried out various studies on defining the composition, properties and the clarification of koruk juice (9)(10)(11)(12)(13)(14)(15), on the quality of grape juice and its variability of different storage conditions (16)(17)(18)(19)(20)(21)(22)(23), although there are limited studies concerning the usability of koruk juice for soft drinks manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these benefits are linked to the antioxidant compounds found in grape juice, such as flavonoids (anthocyanins, proanthocyanidins), phenolic acids and resveratrol among others [5,58]. Therefore, grape juice is consumed not only due to its appreciated sensory characteristics but also because it is a cheap source of phenolic compounds that exert beneficial health effects when consumed [59][60][61], as shown in Table 1.…”
Section: Biological Activity Of Phenolic Compounds Present In Grape Jmentioning
confidence: 99%
“…However, Pellegrini et al Studies have indicated that the major constituents of aniseed are anethole, estragole, eugenol, umbelliferon, coumarins [Gülçın et al, 2003]. Grapes are rich in phenolic compounds such as gallic acid, caffeic acid, chlorogenic acid, kaempferol, quercetin [dos Lima et al, 2014]. These phenolic compounds have been considered to have high antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%